A Physical Interpretation of Asymmetric Growth and Decay of the Geomagnetic Dipole Moment. (18th March 2022) - Buffett, B. A.; Avery, M. S.; Davis, W.
Abstract: Observations of relative paleointensity reveal several forms of asymmetry in the time dependence of the virtual axial dipole moment (VADM). Slow decline of the VADM into a reversal is often followed by a more rapid rise back to a quasi‐steady state. Asymmetry is also observed in trends of VADM during times of stable polarity. Trends of increasing VADM over time intervals of a few 10s of kyr are more intense and less frequent than decreasing trends. We examine the origin of this behavior using stochastic models. The usual (Langevin) model can account for asymmetries during reversals, but it cannot reproduce the observed asymmetry in trends during stable polarity. Better agreement is achieved with a different class of stochastic models in which the dipole is generated by a series of impulsive events in time. The timing of each event occurs randomly as a Poisson process and the amplitude is also randomly distributed. Predicted trends replicate the observed asymmetry when the generation events are large and the recurrence time is long (typically longer than 3 kyr). Large and infrequent generation events argue against dipole generation by small‐scale turbulent flow. Instead, the observations favor a mechanism that relies on expulsion of poloidal magnetic field from the core. Plain Language Summary: Fluctuations in the strength of the Earth's dipole field are a consequence of turbulent fluid motions in the liquid metal core. A quantitative description of this motion is beyond reach, but we can characterize its influence on the time evolution of the dipole field using a suitably defined random process. Stochastic models offer a practical strategy for dealing with poorly known small‐scale dynamics, but the usual (Langevin) model is unable to account for asymmetry between the growth and decay of the dipole. We explore an alternative model in which the dipole is generated by a series of impulsive events. Both the timing and the amplitude of the generation events are random. We show that the model exhibits asymmetry between growth and decay of the dipole. Estimates of the typical time between generation events offer insights into the nature of the fluid motions. We also show that many other features of the model, including reversal rates, are well approximated using the usual Langevin model. This correspondence establishes a physical basis for the Langevin model. Key Points: Trends in paleointensity are asymmetric on timescales of about 10 4  years A stochastic model with random dipole generation reproduces the asymmetry Dipole generation is attributed to infrequent configurations of fluid flow